Impact of Treatment With Biologic Agents on the Use of Mechanical Devices Among Rheumatoid Arthritis Patients in a Large US Patient Registry. Issue 7 (July 2016) - Strand, Vibeke; Greenberg, Jeffrey D.; Griffith, Jenny; Bao, Yanjun; Saunders, Katherine C.; Garg, Vishvas; Li, Guo; Ganguli, Arijit
Abstract : Objective: To assess trends and predictors of mechanical devices/aids use by rheumatoid arthritis (RA) patients since the introduction of biologic disease‐modifying antirheumatic drugs (DMARDs). Methods: Sociodemographic characteristics, disease characteristics, and mechanical aid use (assessed using the Health Assessment Questionnaire) were compared among RA patients ages >17 years at diagnosis, enrolled in the Consortium of Rheumatology Researchers of North America (CORRONA) registry during January 2001 to December 2003 and January 2010 to December 2012. Univariate and multivariate logistic regression analyses were used to identify predictors of mechanical aid use among patients in both cohorts. Results: Sociodemographic characteristics were similar between 1, 096 patients in the 2001–2003 cohort and 11, 140 patients in the 2010–2012 cohort. Disease activity was significantly lower among patients in the 2010–2012 cohort (mean ± SD Clinical Disease Activity Index score 10.1 ± 11.1 versus 17.0 ± 13.8; P  < 0.001). A greater proportion of patients in the 2010–2012 cohort received biologic DMARDs (50.7% versus 32.5%; P  < 0.001) and fewer were biologic‐naive (39.1% versus 61.6%; P  < 0.001). Fewer patients in the 2010–2012 cohort used any mechanical devices/aids (31.1% versus 40.8%; P  < 0.001). In multivariate analysis, patients in the 2010–2012 cohort and those with a history of biologic agent use were less likely to use devices/aids (odds ratio [OR] 0.77 [95% confidence interval (95% CI) 0.66–0.90] and OR 0.68 [95% CI 0.62–0.75], respectively). Predictors of greater devices/aids usage included older age, female sex, higher disease activity, and less employment. Effect sizes were greatest for disease activity and employment. Conclusion: Mechanical devices/aids use among patients with RA was significantly lower during 2010–2012 versus 2001–2003 and among biologic‐experienced patients, suggesting reduced disability.